The processing and treatment of other types of oil palm biomass. - Hisham Hamid, Norul; Abu Bakar, Mohd Supian; Ahmad Ludin, Norasikin; Abdullah, Ummi Hani; Najm, Asmaa Soheil (Elsevier, 2022)
This chapter discusses the problem constraint regarding the other oil palm biomass wastes generate after processing the crude oil palm. The palm oil mill affluent (POME) is the most significant water pollution source in oil palm mills. Many efforts have been made to treat the POME and clean the water and in the same time converts it to other valuable by products. The common way to treat POME are including biological, nonbiological, and integrated system methods. The byproduct generates from POME such as methane gas, biohydrogen, waste organic granule, and polyhydroxyalkanate (PHA) are also discussed in this chapter. It can be concluded the POME waste has a great potential to produce the PHA and biohydrogen as another source of income to the oil palm mills. The commercialization of these by products will have a return on investment and eliminate waste from the POME treatment plant.